Research on the user comprehensive energy consumption decision-making method based on the evolutionary game - Zhu, Xian Feng; Yao, Jun Wei; Xie, Qiong Yao; Dai, Lu; Yang, Chu Yuan; Wang, Hai Liang; He, Qi; Deng, Ling; Shen, Ran; Zhou, Xiao Xia (Frontiers in Energy Research, 2022)
With the increasing diversification of human energy consumption forms in the integrated energy market, analyzing the comprehensive energy consumption behavior of user groups ac-cording to the changing characteristics of their energy demand is an important issue that needs to be urgently addressed. To solve this problem, an analysis method of user's comprehensive energy consumption behavior based on the evolutionary game is proposed in this paper. Firstly, considering three types of users that include residents, large industry, and commercial users, a utility model which takes into account energy consumption characteristics of users and user comfort factors is constructed based on subjective and objective combination weighting method.Then, evolutionary game theory is used to analyze the dynamic selection process for users selecting energy suppliers and the selection results when the evolutionary equilibrium is reached; finally, the model is solved by distributed iterative method. The correctness and validity of the proposed method are verified by the simulation results.